European Citizens' Initiative: A Tool for Engagement and Active Citizenship Workbook ECI from A to Z - Pacheco, Yilly Vanessa (Universitätsverlag Göttingen, 2023)
This publication gathers contributions to understand better and further develop the European Citizens' Initiative. This participatory and agenda-setting tool introduced into the Treaty of Lisbon has not yet reached its full potential of citizen engagement, nor has it driven the significant policy changes initially expected. Bearing this in mind, the project ECI: From A to Z aimed to promote the knowledge and use of the European Citizens' Initiative within the higher education arena by engaging investigators and students from four different Universities (University of Coimbra; Georg-August University of Göttingen; Alexandru Ioan Cuza University of Iaşi and the University of Vigo) to work together to share their concerns and common views on the European Union role and policies. This publication describes the methodology followed and results reached under the project, but more than that, it is a practical toolkit for all who wish to know more about the European Citizens' Initiative and how to put it in motion.